TRPC1 channel clustering during store-operated Ca2+ entry in keratinocytes - Manning, Declan; Barrett-Jolley, Richard; Evans, Richard L.; Dart, Caroline (Frontiers in Physiology, 2023)
Skin is the largest organ in the human body with 95% of its surface made up of keratinocytes. These cells maintain a healthy skin barrier through regulated differentiation driven by Ca2+-transcriptional coupling. Many important skin conditions arise from disruption of this process although not all stages are fully understood. We know that elevated extracellular Ca2+ at the skin surface is detected by keratinocyte Gq-coupled receptors that signal to empty endoplasmic reticulum (ER) Ca2+ stores. Orai channel store-operated Ca2+ entry (SOCE) and Ca2+ influx via ‘canonical’ transient receptor potential (TRPC)-composed channels then activates transcription factors that drive differentiation. While STIM-mediated activation of Orai channels following store depletion is well defined, how TRPC channels are activated is less clear. Multiple modes of TRPC channel activation have been proposed, including (i) independent TRPC activation by STIM, (ii) formation of Orai-TRPC-STIM complexes, and (iii) the insertion of constitutively-active TRPC channels into the membrane during SOCE. To help distinguish between these models, we used high-resolution microscopy of intact keratinocyte (HaCaT) cells and immunogold transmission electron microscopy (TEM) of HaCaT plasma membrane sheets. Our data shows no evidence of significant insertion of Orai1 or TRPC subunits into the membrane during SOCE. Analysis of TEM data shows that during store-depletion and SOCE, Orai1 and TRPC subunits form separate membrane-localized clusters that migrate towards each other. This clustering of TRPC channel subunits in keratinocytes may support the formation of TRPC-STIM interactions at ER-plasma membrane junctions that are distinct from Orai-STIM junctions.